Developement of the vocational interest inventory for technical career and jobs - Vicuña Peri, Luis A. (2002)
The present investigation was oriented to elaborates you the Inventory of Interests toward Technical Careers and of Position, for which was explored the schools, centers and institutes that offer craft and technological training, with it 1 am grouped technological areas that served to plan the content validity procedure performed by technicians qualified with not smaller experience of five years, and by psychologists specialists in consejería and vocational advising, by this Procedure the inventory showed their validity likewise by the method of construct, where is verified that the areas contemplated plows independent and that dog be regrouped in four greater areas, fact that facilitates the application because permits us to reduces the number of ítemes of the inventory.